Heat Shock Protein 70 Serum Levels Differ Significantly in Patients with Chronic Hepatitis, Liver Cirrhosis, and Hepatocellular Carcinoma - Gehrmann, Mathias; Cervello, Melchiorre; Montalto, Giuseppe; Cappello, Francesco; Gulino, Alessandro; Knape, Clemens; Specht, Hanno M.; Multhoff, Gabriele (Frontiers in Immunology, 2014)
Members of the heat shock protein 70 (HSP70) family play an important role in assisting protein folding, preventing protein aggregation and transport of proteins across membranes under physiological conditions. Following environmental (i.e. irradiation, chemotherapy), physiological (i.e. cell growth, differentiation) and pathophysiological (i.e. inflammation, tumorigenesis) stress, the synthesis of HSPs is highly up-regulated, whereas protein synthesis in general is reduced. In contrast to normal cells, many tumor entities including hepatocellular carcinomas (HCC) overexpress Hsp70, the major-stress-inducible member of the HSP70 family, present it on their cell surface and secrete it into the extracellular milieu. Herein, the prognostic relevance of serum Hsp70 levels in patients with chronic hepatitis (CH; n=50), liver cirrhosis (LC; n=46), and hepatocellular carcinoma (HCC; n=47) was analyzed. Similar to other tumor entities, Hsp70 is also present on the surface of primary HCC cells. The staining intensity of intracellular Hsp70 in HCC tissue is stronger compared to control and cirrhotic liver sections. Hsp70 serum levels in all HCC patients were significantly higher compared to a control group without liver disease (n=40). No significant age- and gender-related differences in Hsp70 serum levels were observed in male and female healthy human volunteers (n=86). Patients with chronic hepatitis (CH, n=50) revealed significantly higher Hsp70 serum levels compared to the control group, however, these values were significantly lower than those of HCC patients (n=47). Furthermore, a subgroup of patients with LC who subsequently developed HCC (LC-HCC, n=13) revealed higher Hsp70 serum levels than patients with LC (n=46, p=0.05). These data indicate that serum Hsp70 levels are consecutively increased in patients with chronic hepatitis, liver cirrhosis and liver carcinomas and thus might have a prognostic value.